Microwave Properties and Conductivity Anisotropy of Oriented Multiwalled Carbon Nanotube/Epoxy Composites - Vovchenko, L.L.; Zagorodnii, V.V.; Yakovenko, O.S.; Matzui, L.Yu.; Oliynyk, V.V.; Launets, V.L. (Металлофизика и новейшие технологии, 2016)
Epoxy composites with the aligned network of multiwalled carbon nanotubes generated by applying AC electric field during the curing process are fabricated. Industrial nanotubes with diameter of 10—30 nm and length of 10—30 μm are used. The nanotubes’ concentration is varied from 0.2 to 1.0% wt. DC conductivity is measured for two orientations of multiwalled carbon nanotubes’ network–parallel and perpendicular to the direction of the instrument current. Similarly, complex microwave permittivity and conductivity are investigated for parallel and perpendicular orientations of multiwalled carbon nanotubes’ network to the microwave electric field. Measured DC conductivity of order of 10⁻⁷—10⁻⁵ S/m contrasts with microwave conductivity of order of 10⁻²—10⁻¹ S/m. The conductivity anisotropy varies from 18 to 26 for DC measurements and from 1.26 to 2.04 for microwave ones. Such difference in anisotropies can be attributed to the essential inequality of the actual electron transport mechanisms under DC and microwave electric fields.